The immunogenetics of primary biliary cirrhosis: A comprehensive review. (November 2015) - Webb, G.J.; Siminovitch, K.A.; Hirschfield, G.M.
Abstract: Primary biliary cirrhosis (PBC), a classic autoimmune liver disease, is characterised by a progressive T cell predominant lymphocytic cholangitis, and a serologic pattern of reactivity in the form of specific anti-mitochondrial antibodies (AMA). CD4+ T cells are particularly implicated by PBC's cytokine signature, the presence of CD4+ T cells specific to mitochondrial auto-antigens, the expression of MHC II on injured biliary epithelial cells, and PBC's coincidence with other similar T cell mediated autoimmune conditions. CD4+ T cells are also central to current animal models of PBC, and their transfer typically also transfers disease. The importance of genetic risk to developing PBC is evidenced by a much higher concordance rate in monozygotic than dizygotic twins, increased AMA rates in asymptomatic relatives, and disproportionate rates of disease in siblings of PBC patients, PBC family members and certain genetically defined populations. Recently, high-throughput genetic studies have greatly expanded our understanding of the gene variants underpinning risk for PBC development, so linking genetics and immunology. Here we summarize genetic association data that has emerged from large scale genome-wide association studies and discuss the evidence for the potential functional significance of the individual genes and pathways identified; we particularly highlight associations in the IL-12-STAT4-Th1 pathway. HLA associations and epigenetic effects are specifically considered and individual variants are linked to clinical phenotypes where data exist. We also consider why there is a gap between calculated genetic risk and clinical data: so-called missing heritability, and how immunogenetic observations are being translated to novel therapies. Ultimately whilst genetic risk factors will only account for a proportion of disease risk, ongoing efforts to refine associations and understand biologic links to disease pathways are hoped to drive more rational therapy for patients. Highlights: Primary biliary cirrhosis is a typical autoimmune disease with a strong genetic component. Genome-wide studies have greatly expanded understanding of genetic risk. This review highlights individual associations including HLA types and the IL-12-STAT4 pathway. Animal models, epigenetics and novel immunological therapies are also considered.